Role of Vibronic Coupling for the Dynamics of Intersystem Crossing in Eu3+ Complexes: an Avenue for Brighter Compounds - Saraiva, Leonardo F. [UNESP]; Carneiro Neto, Albano N.; Bisp, Airton G.; Quintano, Mateus M.; Kraka, Elfi; Carlos, Luís D.; Lima, Sergio A. M. [UNESP]; Pires, Ana M. [UNESP]; Mour, Renaldo T. (American Chemical Society (ACS), 2025)
Understanding the dynamics of photophysical processes in Ln3+ complexes remains challenging due to the intricate nature involving the metallic center, where sensitization (antenna effect) plays a pivotal role. Current studies have often overlooked the vibronic coupling within the antenna effect, leading to incomplete insights into excited-state dynamics. To address these shortcomings, we introduce a novel theoretical and computational approach that leverages the impact of the vibrational modes of the S1 and T1 states in this effect through the correlation function formalism, offering a comprehensive view of intersystem crossing (ISC). Our approach achieves a desirable alignment between empirical and theoretical rates, outperforming previously employed semiclassical methods. A groundbreaking finding is that vibronic coupling with vibrations in the 700-1600 cm-1 energy range is crucial for higher ISC, and local vibrational mode analysis identified that this process is driven by delocalized vibrations across the molecule. These results shed light on the key molecular fragments responsible for vibronic coupling, opening an avenue for harnessing faster ISC by tailoring the ligand scaffold. Overall, it also demonstrates how ISC dynamics can serve as a bridge between theory and experiment, furnishing detailed mechanistic insights and a roadmap for the development of brighter compounds.